Improving the Trigonometric Functions Learning Concept with Dynamic Mathematics Software - Li, Li; Pereira, Jerito; Hermita, Neni (International Journal of Scientific Research and Management (IJSRM), 2022)
Since the 21st century, the new model of Internet+Education has gradually penetrated into the field of mathematics education and has become a hot topic in the current research on mathematics education, and education informatization has become the main development trend. Therefore, the purpose of this research is to help students and teachers how to use Hawgent dynamic mathematics software to help students learn trigonometric functions and help teachers practice trigonometric functions. The research method used is the research and development (R&D) method and this research was done at Chongqing Zhongxian Senior Middle School for the period month of July to August 2021. The model has adaptive guiding principles that can help researchers develop ICT based learning media in the five stages of analysis, design, development, implementation, and evaluation. This research is based on the Hawgent dynamic mathematics software to design a trigonometric function integrable ware design model, dynamically presenting the concept of trigonometric function and its image and properties, and then use integrable ware to assist the teaching of trigonometric functions, and verify it through experimental teaching. The results show that the learning of trigonometric functions assisted by Hawgent dynamic integrable ware design can help improve students' understanding and interest in trigonometric functions. In the future, other researchers can study the influence of information technology on the teaching of mathematical formulas, theorems, and mathematical problem solving, and explore SEM models of influencing factors.